The growing challenge of major trauma in older people: a role for Comprehensive geriatric Assessment?. (10th March 2017) - Fisher, James Michael; Bates, Charlotte; Banerjee, Jay
Abstract: In this commentary article, we describe the impact that an ageing population is having on the nature of major trauma seen in emergency departments. The proportion of major trauma victims who are older people is rapidly increasing and a fall from standing is now the most common mechanism of injury in major trauma. Potential barriers to effective care of this patient group are highlighted, including: a lack of consensus regarding triage criteria; potentially misleading physiological parameters within triage criteria; non-linear patient presentations and diagnostic nihilism. We argue that the complex ongoing care and rehabilitation needs of older patients with major trauma may be best met through Comprehensive Geriatric Assessment (CGA). Furthermore, the use of frailty screening tools may facilitate more informed early decision-making in relation to treatment interventions in older trauma victims. We call for geriatric medicine and emergency medicine departments to collaborate—equipping urgent care staff with the basic competencies necessary to initiate CGA should be a priority, and geriatricians have a key role to play in delivery of such educational interventions.